Research on Strategies of Vocational Education to Help Rural Revitalization - Junhao Lan; Nur Fauziyah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2025)
Since the 18th National Congress, China has prioritized rural development, emphasizing vocational education as crucial for cultivating skilled professionals and addressing rural challenges. Rural areas face persistent talent shortages, creating strong synergies between vocational education and revitalization efforts. National policies explicitly position vocational education as instrumental in training new professional farmers and supporting rural development strategies. This research focuses on Baoshan Vocational College as a case study, employing lifelong education theory, human capital theory, and Foster's rural education framework. The study examines domestic and international models of vocational education supporting rural development through comparative case analysis, surveys, and field investigations. The research explicitly assesses training needs among local farmers and identifies gaps in current vocational education programs. Building on these findings, the study proposes practical strategies for optimizing the college's resources to serve rural revitalization better. The outcomes aim to enhance institutional development, support regional revitalization, and contribute to broader theoretical and practical knowledge. Ultimately, this research provides valuable insights for policymakers developing vocational education strategies and implementing comprehensive rural revitalization initiatives.